Neuromuscular responses triggered by continuous and intermittent running to exhaustion - Diefenthaeler, F.; Dittrich, N.; de Lucas, R. D.; Guglielmo, L. G. A. (International Calgary Running Symposium, August 14-17, 2014, 2014)
The aim of the present study was to evaluate the effects of fatigue on neuromuscular responses from a running to exhaustion performed at the maximal lactate steady state intensity during continuous and intermittent protocols. Methods: Twelve runners performed an incremental treadmill test, several constant speed tests to determine the maximal lactate steady state at continuous and intermittent (exercise:rest ratio of 5:1) models and two randomized tests until exhaustion at such intensities. Knee extension torque and electromyographic activity (EMG) of the vastus lateralis (VL) and rectus femoris muscles during maximal unilateral isometric knee extensions were collected before and immediately after the time to exhaustion tests. The sum of the root mean square (RMS) values of both muscles was used as an index of the total muscle activation. Muscle activity and the torque values were normalized and used to calculate the EMG/torque ratio. A paired t-test for comparisons between pre and post values for each condition (continuous and intermittent) was used to detect the differences in the analyzed variables. Significance was set at P<0.05. Results: There was a significant decrement (¡«15%) in torque production and EMG activity after time to exhaustion tests for both exercise models. No differences were observed for EMG/torque ratio and median frequency (MDF) for VL and RF (Table 1). Conclusion: Results suggest that the type of fatigue observed in the present study for both running models could be categorized as central due to a constant EMG/torque ratio associated with a torque decrement.